IENE 9 project: Developing a culturally competent and compassionate LGBT + curriculum in health and social care education - Pezzella, Alfonso; Pistella, Jessica; Baiocco, Roberto; Kouta, Christiana; Rocamora-Perez, Patricia; Nielsen, Dorthe; Kuckert-Wöstheinrich, Andrea; Dudau, Victor; Papadopoulos, Irena (My University, 2022)
Introduction: The IENE projects (2008–2022) aim to promote a model for developing intercultural dialogue and enhance the ability to provide culturally competent and compassionate care for the health and social care professionals at national and European levels. The IENE 9 project, named “Developing a culturally competent and compassionate LGBT + curriculum in health and social care education,” builds on the work developed in the previous IENE projects and emphasizes the importance of addressing LGBT + issues in health and social care education. Method: Through an innovative Massive Open Online Course (MOOC), professionals will learn the skills to work toward building an LGBT + inclusive health and social care system. Result: Notwithstanding the progress made in recent years on LGBT + issues, research indicates that too little attention has been given to LGBT + needs in health and social care settings, and these remain substantial issues that are often ignored. Conclusion: This letter to the editor aims to present the IENE 9 project given that greater efforts are needed to improve professionals’ skills regarding sexual and gender minority population. We strive to continue our efforts in promoting the well-being and mental health of LGBT + people in health and social care education.
Keywords: LGBT+; Compassionate curricula; Health and social care; Research; Intercultural education